Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta - Supriati H. Rahayu; Hilman Haroen; TW Budiutomo; Nginayatul Khasanah; Nuryati Nuryati (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2020)
Qualitative research on the quality of Quran education services has a specificity according to the character of the material that prioritizes recitation and reading recitation, especially for TQA education organized by the Tadarus Team Foundation for the Young Generation Mosque and Musholla (YTT